Dynamics, structure and assembly of the basement membrane in developing salivary glands revealed by an exogenous EGFP-tagged nidogen probe. (11th August 2022) - Kadoya, Yuichi; Futaki, Sugiko; Shimono, Chisei; Kimura, Taketoshi; Sekiguchi, Kiyotoshi
Abstract: Most epithelial tissues rapidly become complex during embryonic development while being surrounded by the basement membrane (BM). Thus, the BM shape is thought to change dramatically as the epithelium grows, but the underlying mechanism is not yet clear. Nidogen-1 is ubiquitous in the BM and binds to various other BM components, including laminin and type IV collagen. To elucidate the behavior of the BM during epithelial morphogenesis, we attempted to live-label the developing BM with recombinant human nidogen-1 fused to an enhanced green fluorescent protein (hNid1-EGFP). Submandibular glands of mouse embryos were cultured in glass-bottomed dishes and incubated in media containing hNid1-EGFP. Subsequent confocal microscopy clearly visualized the BMs surrounding the epithelial end buds. On three-dimensional reconstruction from Z-series confocal sections, the epithelial BM was observed as a thin sheet that expanded continuously around the entire epithelial basal surface. Because the explants continued to grow well in the presence of hNid1-EGFP, time-lapse confocal microscopy was performed to follow the dynamics of the BM. We found that the epithelial BM is an adaptive structure that deforms in accordance with the rapid shape changes of the developing epithelium. Furthermore, hNid1-EGFP was found to be incorporated differently into the epithelial BM compared with that reported for fibronectin or type IV collagen, suggesting that individual BM components assemble in different ways to form the BM.